2020
DOI: 10.1038/s41598-020-68370-y
|View full text |Cite|
|
Sign up to set email alerts
|

Novel antimicrobial phosphate-free glass–ceramic scaffolds for bone tissue regeneration

Abstract: In this study a phosphate-free glass-ceramic porous scaffold was synthesized by a three-step methodology involving slurry preparation, induction of porosity by surfactant-assisted foaming following by freeze-drying and sintering. This inorganic scaffold was characterized by X-ray diffraction, scanning electron microscope (SEM), degradation and bioactivity. Thermal treatment at 750 °C showed two new crystalline phases, combeite and nepheline, into the glassy matrix responsible for its properties. The cell respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Improving tissue restoration and preventing bacterial infection are favorable properties for bone biomaterials 2 , 3 . The prior study showed that LAP-functionalized PLA nanofibers could significantly enhance the proliferation and osteodifferentiation of hBMSCs without any external osteoinductive factors 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improving tissue restoration and preventing bacterial infection are favorable properties for bone biomaterials 2 , 3 . The prior study showed that LAP-functionalized PLA nanofibers could significantly enhance the proliferation and osteodifferentiation of hBMSCs without any external osteoinductive factors 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Infection control is one of the leading clinical issues related to regeneration surgery in bone tissue engineering 1 . An ideal bone scaffold will presumably be multifunctional, combining different functionalities to simultaneously promote bone regeneration while also limiting microbial infection 2 , 3 . Replacing traditional manners such as systemic antibiotic administration with the incorporation of antibiotics in scaffolds can be an effective treatment for bone infections 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nepheline can also be found as a crystalline phase developed by heat treatment during the manufacturing process of different materials. For instance, in recent years, glass–ceramic materials containing nepheline have been documented as efficient UltraViolet Light Emitting Diode (UV‐LED) color converters, 4 scaffolds for bone tissue regeneration 5 or for dental applications 6 . Nepheline is also reported in geopolymers, 7 self‐compacting repair mortars, 8 low thermally conductive ceramic foams, 9 or traditional ceramics 10 .…”
Section: Introductionmentioning
confidence: 99%
“…P 2 O 5 -free BGs, that is, from the groups SiO 2 -CaO and SiO 2 -CaO-Na 2 O have shown to be highly advantageous. [6][7][8] These BGs have been shown to be bioactive 6,9,10 and capable of inducing extracellular matrix (ECM) secretion and mineralization by primary human osteoblasts (OBs). 7 In addition, P 2 O 5 -free BG may be particularly useful to some fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%